The Encyclopedia of Northern Kentucky - Claypool, James C.; Tenkotte, Paul A. (Book collections on Project MUSE., 2009)
Covers Boone, Kenton, Campbell, Carroll, Gallatin, Owen, Grant, Pendleton, Bracken, Robertson, and Mason counties of Kentucky.